P352 HEALTH SURVEILLANCE FOR ENTRY INTO THE CARDIOLOGY DEPARTMENT IN TIMES OF SARS–COV2 PANDEMIC. (18th May 2022) - Cappannelli, S; Tedesco, T; Fischer, B; Capponi, E; Buccolieri, M; Cardile, M; Cosmi, D; Di Pasquale, T; Martinelli, S; Pagnotta, F; Piccioni, N; Rey, L; et al.
Abstract: Introduction: The SARS–Cov2 pandemic has made it necessary to implement drastic measures to contain the infection and at the same time start a regulated process of protection of health workers (OS) and hospitalized patients (PR). Objective: To verify the effectiveness of the health surveillance measures for SARS–COoV2 infection put in place to protect the OS and PR in the Cardiology of the Gubbio–Gualdo Tadino Hospital (AUSL Umbria 1). Material and methods: we conducted a retrospective analysis, in the period 1 April 2020– 30 November 2021, on OS and PR in our Cardiology–UTIC OU. The protocols used for health surveillance provided, in all phases of the pandemic, the well–known general prevention measures (PPE, hand hygiene, distancing, per–triage). In phase 1 of the pandemic, molecular swabs were also carried out every 14 days at the OS and only at the entrance to the PR, in phase 2 antigenic tests every 5 days at the OS and molecular swabs at the entrance and after 48 hours at the PR while in the current phase 3 an antigenic test every 10 days at the OS and PR a molecular swab at T0 and T2 and an antigenic test at the 5th day and subsequently every 5 days. Results: A total of 320 subjects, a sample of PR (300, 15 patients month) and all OS (20) were analyzed. A total of 2658 swabs were carried out (1088 molecular and 1570 antigenic) and only two positive OS were found in phase 1 of the pandemic alone, while in phase 2 and 3 no OS or PR was positive. Conclusions: The application of the general rules for the prevention of SARS–Cov2 infection and the definition of precise intra–hospital pathways, together with the application of a hospital health surveillance protocol, has made it possible to significantly limit infections within the OU. In addition, the rapid identification of positive OS allowed for rapid isolation avoiding the spread of infection to PR and other OS. Bibliography: COVID and gender resources. Johns Hopkins Bloomberg School of Public Health. https://coronavirus.jhu.edu/map.html ISS, National Survey on COVID–19 contagion in residential and social health structures, 30 March 2020; Guidelines for health activities in phase 1, phase 2 and phase 3 of the pandemic. Umbria Region.